2018
DOI: 10.3846/btp.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Attributes and Audit Quality: A Benchmark Analysis

Abstract: This study examined audit committee attributes and audit quality with emphasis on the specific requirements of the 2011 SEC code. The study applied the deductive approach via the expost facto research design and the Binary probit regression model in analyzing the various hypotheses put forward in study. Data used for the study were gathered for 150 firm-year observations from the annual reports of quoted companies on the floor of the Nigerian Stock Exchange. Findings from the study revealed that audit committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 30 publications
9
27
0
2
Order By: Relevance
“…Corporate diversity has so much influence on the quality of the board (Kruger, 2007;Osariemen et al, 2018). Diversity would foster conflict of interest, different opinion, and knowledge, but all these shortfalls are considered ideal for a good board composition aimed at providing quality and value of organization decision-making process geared toward improving the level of environmental disclosure (Carter, Simkins, & Simpson, 2003;Jackson, Joshi, & Erhardt, 2003).…”
Section: Corporate Diversitymentioning
confidence: 99%
“…Corporate diversity has so much influence on the quality of the board (Kruger, 2007;Osariemen et al, 2018). Diversity would foster conflict of interest, different opinion, and knowledge, but all these shortfalls are considered ideal for a good board composition aimed at providing quality and value of organization decision-making process geared toward improving the level of environmental disclosure (Carter, Simkins, & Simpson, 2003;Jackson, Joshi, & Erhardt, 2003).…”
Section: Corporate Diversitymentioning
confidence: 99%
“…Ma and C. Ma (2011) and Moeller (2011) concluded that the basis of COSO framework consists of five dimensions including the control environment, risk assessment, control activity, information and communication, and monitoring. Prior accounting research revealed that audit committee effectiveness is associated with financial reporting reliability (Asiriuwa, Aronmwan, U. Uwuigbe, & O. R. Uwuigbe, 2018;Kamolsakulchai, 2015;Klai, 2011;Schneider, Gramling, Hermanson, & Ye, 2009;Ashbaugh-Skaife, Collins, & Kinney, 2007). Hasan et al (2014), Spatacean (2012), and Jokipii (2010) suggested that audit committee effectiveness is providing reasonable assurance regarding the reliability of financial reporting.…”
Section: Audit Committee Effectiveness and Financial Reporting Reliabmentioning
confidence: 99%
“…Audit committee effectiveness refers to effective team of audit committee which is set and designed to prevent fraud in financial statement, prevent assets loss, and conduct its operation in an efficient and effective manner (Asiriuwa et al, 2018;Johnson et al, 2012;Jokipii, 2010;Altamuro & Beatty, 2010). Asiriuwa et al (2018) revealed that audit committee attributes include audit committee size, frequency of meetings, number of expertise, and overall effectiveness. Audit committee effectiveness is measured using three-item scale modified from Asiriuwa et al (2018), Johnson et al (2012), Jokipii (2010), and Altamuro and Beatty (2010).…”
Section: Questionnaire Development and Variable Measurementmentioning
confidence: 99%
See 2 more Smart Citations